Spazio pubblico e zone di transizione - Bressan, Massimo (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
New transition zones are emerging with various shapes and compositions between urban centers and remote areas: from the memorable examples of Chicago in the early twentieth century to the widespread urbanization of many areas of central and northern Italy. Production processes and global connections bringing cities and regions into the flow of cultural and economic change grow there. The study of Prato – examined from an ethnographic and typically urban perspective - aims to shed light a) on the current transformation of urban and social fabric long characterized by mixité between work time and free time and between industrial space and residential space; b) on the perception of safety; c) on the dynamics of segregation and denial of the city; d) on the possible interpretations of space and everyday life.